"Having fellowship with God" according to 1 John: dealing with the intermediation and invironment through which and in which it is constituted - D. G. van der Merwe (Acta Theologica)
For believers to have fellowship with one another and corporately with God, is one of the main objectives stated for the proclamation of the gospel by the author of 1 John. This article investigates the intermediation and environment through which and in which fellowship is constituted between God and his children. From the prooemium (1:1-4) of the epistle, which is used as the basic text in this research, Jesus Christ, the Son of God, has been designated to accomplish a fundamental revelatory-salvific act to enable believers to have fellowship with God and one another. This concept of fellowship, used in a familial sense, is described from the symbolic narrative of family life where God is the “Father”, Jesus is “his only Son” and believers are the “children of God”. 1 John underlines the autonomy of the individual child of God (2:20, 27; 5:20), but qualifies this emphasis with the thematic development of the concept of fellowship with other believers in the familia dei. The joy of believers in this familia dei, as an outcome of this fellowship, only becomes “complete” where fellowship is constituted both among God’s children and corporately with God.